Upstream Regulators of Fibroblast Growth Factor 23 - Ratsma, Danielle M. A.; Zillikens, M. Carola; van der Eerden, Bram C. J. (Frontiers in Endocrinology, 2021)
Fibroblast growth factor 23 (FGF23) has been described as an important regulator of mineral homeostasis, but has lately also been linked to iron deficiency, inflammation and erythropoiesis. FGF23 is essential for the maintenance of phosphate homeostasis in the body and activating mutations in the gene itself or inactivating mutations in its upstream regulators can result in severe chronic hypophosphatemia, where an unbalanced mineral homeostasis often leads to rickets in children and osteomalacia in adults. FGF23 can be regulated by changes in transcriptional activity or by changes at the post-translational level. The balance between O-glycosylation and phosphorylation is an important determinant of how much active intact or inactive cleaved FGF23 will be released in the circulation. In the past years, it has become evident that iron deficiency and inflammation regulate FGF23 in a way that is not associated with its classical role in mineral metabolism. These conditions will not only result in an upregulation of FGF23 transcription, but also in increased cleavage, leaving the levels of active intact FGF23 unchanged. The exact mechanisms behind and function of this process are still unclear. However, a deeper understanding of FGF23 regulation in both the classical and non-classical way is important to develop better treatment options for diseases associated with disturbed FGF23 biology. In this review, we describe how the currently known upstream regulators of FGF23 change FGF23 transcription and affect its post-translational modifications at the molecular level.